Uniformity Trials On Colocasia (Colocasia esculenta L.) - Lizy M J (Department of Statistics, College of Veterinary and Animal Sciences, 1986)
A uniformity trial on colocasia was conducted at the experimental field of the College of Agriculture, Vellayani during the period April – September 1984, to study the nature and magnitude of soil heterogeneity and to estimate the optimum size and shape of plots in conducting field trials on colocasia. The various techniques adopted for achieving these objectives were, productivity contour map, mean squares among strips, serial correlation, heterogeneity index method and maximum curvature method. The biometrical observations such as height, girth, yield number of leaves and leaf area were taken from all plants. Productivity contour map revealed that the field was heterogeneous with regard to soil fertility. The mean squares for the horizontal and vertical arrangements indicated that the fertility was more clear along the length than along the width of the field. The low serial correlation coefficients for both rows and columns established that fertile areas occur in patches. The coefficient of variation increased in plot size. For a given size of the plot, the long and narrow plots yield lower coefficient of variation than square plots. The Smith’s variance law in the form Y = ax-b gave a satisfactory fit to the data. But among all the fitted models the equation Y = a + b/ x1/2 + c/x was found to be the best. Generalisation of Smith’s law in the form Y = ar-g 1c-g 2 also gave a good fit to the data and heterogeneity of rows was found to be significantly more than that of columns. The optimum plot size found out by using Smith’s equation was 12 units (3.34m2). But the optimum plot size computed by using the optimum equation Y = a + b/x1/2 + c/x was 10.87 units (2.93m2). A study of the optimum plot size while considering the cost of experimentation using the Smith’s equation was 1.636m2. In general, it can be recommended that a plot of 2.93m2 as optimum for conducting field trials on colocasia.